Possibilities of Using the Potential of Ocean Thermal Energy in the Waters near the Borders of Mozambique - Fabião, A. W.; Mitrani, I.; Cabrales, J. (Revista Cubana de Física, 2018)
The present work explores the possibility of applying electricity generation technologies from the energy of the oceanic thermal gradient in the Mozambique Channel. For the preparation of this research, the annual surface temperature of 1981-2016 and monthly for 2016 were analyzed. For OTEC application, a temperature difference of about 20 o C between the surface and a lower level is necessary. Depth not greater than 1000 m. using ocean data from NOAA, GrADS was applied to establish the annual course of ocean surface temperature and its spatial distribution. The favorable conditions for the use of OTEC a long MC in the provinces of Inhambane, Nampula and Cabo Delgado were identified, where surface ocean temperature varies from 24 to 28 o C and in the depth varies from 4.6 to 6.8 o C.